PERAN HUMAN RESOURCE DEVELOPMENT (HRD) DALAM MENINGKATKAN PRODUKTIVITAS KARYAWAN DI PT. YANASURYA BHAKTIPERSADA - Aida Irmawati (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2015)
Work productivity is a work of an employee. The work of this employee is a process of working from a person in producing a good or service. Frequent employee productivity decreases due to the possibility of no good control of work productivity of staff or employees that can cause inconvenience in work, minimal wage and also dissatisfaction in work. A company or organization in improving the productivity of employees also experience constraints. Decrease in work productivity is still common. The problem of work productivity is a common problem that occurs in every company. Sometimes the work productivity of an employee tends to decrease and the effect is the decline of a company. If not addressed properly then the company will tend to experience a significant decline. The problems about the productivity of this work is an indication that the role of management as human resource management is required. This is a way of increasing an employee productivity. Conditions as described above show that human factors play an active role in improving the quality of the company. This is also related to existing technology. Many cases show that technology has advanced but the availability of human resources is very minimal. This is because of the unpreparedness of the organization to make optimal progress. This is supported by Gomez (1997) that human resources play an important and decisive role for organizational success. Work productivity which is the performance of employees as the embodiment is performance appraisal or assessment of work, often experience obstacles. This constraint in the form of assessment work that is not in accordance with the performance of employees.